Modelling and control of an adaptive cruise control system in MATLAB - Fariz Izuan Ya'cob (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Automotif)) - Universiti Teknologi Malaysia, 2006